Concordance of microbial and visual health indicators of white-band disease in nursery reared Caribbean coral Acropora cervicornis - Monica D. Schul; Dagny-Elise Anastasious; Lindsay J. Spiers; Julie L. Meyer; Thomas K. Frazer; Anya L. Brown (PeerJ, 2023)
Background Coral diseases are one of the leading causes of declines in coral populations. In the Caribbean, white band disease (WBD) has led to a substantial loss of Acropora corals. Although the etiologies of this disease have not been well described, characterizing the coral microbiome during the transition from a healthy to diseased state is critical for understanding disease progression. Coral nurseries provide unique opportunities to further understand the microbial changes associated with diseased and healthy corals, because corals are monitored over time. We characterized the microbiomes before and during an outbreak of WBD in Acropora cervicornis reared in an ocean nursery in Little Cayman, CI. We asked (1) do healthy corals show the same microbiome over time (before and during a disease outbreak) and (2) are there disease signatures on both lesioned and apparently healthy tissues on diseased coral colonies? Methods Microbial mucus-tissue slurries were collected from healthy coral colonies in 2017 (before the disease) and 2019 (during the disease onset). Diseased colonies were sampled at two separate locations on an individual coral colony: at the interface of Disease and ∼10 cm away on Apparently Healthy coral tissue. We sequenced the V4 region of the 16S rRNA gene to characterize bacterial and archaeal community composition in nursery-reared A. cervicornis. We assessed alpha diversity, beta diversity, and compositional differences to determine differences in microbial assemblages across health states (2019) and healthy corals between years (2017 and 2019). Results Microbial communities from healthy A. cervicornis from 2017 (before disease) and 2019 (after disease) did not differ significantly. Additionally, microbial communities from Apparently Healthy samples on an otherwise diseased coral colony were more similar to Healthy colonies than to the diseased portion on the same colony for both alpha diversity and community composition. Microbial communities from Diseased tissues had significantly higher alpha diversity than both Healthy and Apparently Healthy tissues but showed no significant difference in beta-diversity dispersion. Our results show that at the population scale, Healthy and Apparently Healthy coral tissues are distinct from microbial communities associated with Diseased tissues. Furthermore, our results suggest stability in Little Cayman nursery coral microbiomes over time. We show healthy Caymanian nursery corals had a stable microbiome over a two-year period, an important benchmark for evaluating coral health via their microbiome.